Costs and Revenues Balance: The Case of Municipal Delegated Competences in Slovakia - Mikušová Meričková, Beáta; Svidroňová Murray, Mária; Bakoš, Eduard; Stejskal, Jan (My University, 2023)
Local authorities' financial resources should be commensurate with the competences provided for by the law. However, in most countries, representatives of local self-governments claim that their total revenues are insufficient to deliver allocated tasks at a standard scale and level of quality. Such statements are somewhat problematic, especially in less-developed countries, where cost-center accounting is not used and service standards are not defined. This paper analyzes the relationship between the costs of delegated competences and the resources provided to cover these costs in Slovakia. We found that Slovak municipalities (with some exceptions) do not know the exact costs of delegated competences, and that the state does not cover the total costs of delegated competences, which contradicts the Slovak constitution. Our short comparison in the discussion shows that the Czech situation is very similar, suggesting that the problem might be common for all post-Soviet countries.
Bilance nákladů a výnosů: Případová studie přenesených kompetencí obcí na Slovensku
Keywords: delegated competences; fiscal federalism; public administration; Slovakia; přenesené kompetence; fiskální federalismus; veřejná správa; Slovensko